Potential Responses to the Coloniality of Human Rights and “Man” in Light of Animal Rights Talk: To Imagine What Never Was - Baldelomar, César (Liberatio, 2024)
Presented as a thought experiment, this essay urges readers to (re)consider how critiques of the colonial concept of man (as a rational being) can disrupt and expand dominant ontologies to birth creative reimaginings of rights talk and protections, especially since rights discourses privilege rationality as the marker of full humanity. The same claims used to debunk animal rights can also be used to debunk human rights, especially for humans lacking a certain cognitive capacity or will. As evident throughout history and in the present, not all flesh and bodies (including hominine ones) are worth the same, notwithstanding aspirational and humanist rhetoric and rights bolstered by colonial and theological concepts. Some “humans” have been and continue to be equated with the savage and with animality — casting doubt on the universal applicability of rights talk as currently framed and deployed. Discussing the potential for animal rights would reconstitute and strengthen human rights — for it would force scholars, activists, judges, lawyers, students and professors to rethink the basis for global and local human rights regimes in light of creative jurisprudences and ontologies not based exclusively on Judeo-Christian or Western paradigms and worldviews. Such project also challenges coloniality and colonialism — the foundational paradigms of “modernity” and existing rights talk. The essay ends with some notes and suggestions on reimagining the human as an important step in demystifying human rights as a universal, eternal paradigm that protects all flesh equally, if at all.